2009
DOI: 10.1039/b815424d
|View full text |Cite
|
Sign up to set email alerts
|

Surface attached manganese–oxo clusters as potential contrast agents

Abstract: Surface attachment of the manganese-oxo cluster known as Mn-12 provided aqueous solution stabilization that allowed investigation of the use of the cluster as an MRI contrast agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…50–53 Mertzman et al recently showed that manganese-oxo clusters offer promise as an MRI contrast agent and their magnetic properties and water solubility are improved when they were conjugated onto the surface of polymer (e.g., polystyrene) beads (Figure 3). 54 Mn-oxo cluster has a large number of unpaired electrons and has four coordinated waters that are exchanged rapidly on the NMR timescale due to the coordination to the labile Mn(III). It can undergo ligand exchange for attachment onto any surface containing carboxylic acid functionality.…”
Section: Contrast Agent Familiesmentioning
confidence: 99%
“…50–53 Mertzman et al recently showed that manganese-oxo clusters offer promise as an MRI contrast agent and their magnetic properties and water solubility are improved when they were conjugated onto the surface of polymer (e.g., polystyrene) beads (Figure 3). 54 Mn-oxo cluster has a large number of unpaired electrons and has four coordinated waters that are exchanged rapidly on the NMR timescale due to the coordination to the labile Mn(III). It can undergo ligand exchange for attachment onto any surface containing carboxylic acid functionality.…”
Section: Contrast Agent Familiesmentioning
confidence: 99%
“…5), as expected from Eq. (9). As the width increases, there are probabilities of selecting much lower values of D than D 0 .…”
Section: B Distributions Of Magnetic Anisotropy Dmentioning
confidence: 99%
“…This was motivated by their applications for magnetic storage media [4,5], biosensors [6], and contrast agents in magnetic resonance imaging [7][8][9]. Ideally, for a given system, magnetic nanoparticles may have uniform particle sizes and shapes, and molecules may have identical ligand orientations.…”
mentioning
confidence: 99%
“…A few approaches were proposed including binding the clusters to polystyrene beads and an emulsion-assisted self-assembly method for dispersing stearic acid modified Mn 12 . 12 While these were viable approaches to use SMM as a T2 weighted (darkening contrast) MRI agent, a more biocompatible, robust methodology is required to use it as a T1 weighted agent (brightening contrast) to diagnose vascular disease. We hypothesized that the induced magnetic moment of Mn 12 clusters in the applied field would accelerate the relaxation of surrounding water protons.…”
mentioning
confidence: 99%